Current and Future Demand for Health Services Researchers: Perspectives from Diverse Research Organizations. (12th June 2018) - Rich, Eugene; Collins, Anna
Abstract : Objective: The Affordable Care Act and Medicare Access and CHIP Reauthorization Act are changing access to, and delivery of, health care in the United States, with potential implications for the field of health services research (HSR). We therefore investigated employers' perceptions of demand for individuals to conduct HSR, the competencies required for success, and implications for HSR training programs. Data Source: Interviews conducted in August 2016 with 21 key informants at a range of U.S.‐based HSR organizations. Study Design: We conducted a semistructured, qualitative, telephone interview study to explore relevant topics. Data Collection/Extraction Methods: Interviews with respondents were transcribed from recordings and then synthesized by respondent organization type and topic area. Principal Findings: Most respondents reported recently hiring health services researchers, and most anticipated hiring additional such researchers in the future. Most respondents emphasized the abilities to analyze data, work in teams, and engage with stakeholders. Finally, most respondents recommended that potential recruits gain real‐world experience during their academic training. Conclusions: Our interviews indicated that current and future demand for health services researchers is strong. They also suggested that, as a field, HSR will continue to draw together individuals from a variety of backgrounds to inform a diverse array of decision makers.